Uncovering Ethical Behavior: A Causal Factors Perspective of Control Systems and Compensation - Wafa, Muhammad Husnul; Ghazali, Muhammad; Hidayati, Rini (Santoso Academy Network, 2024)
This research examines the effects of internal control, compliance, management remuneration, and work ethic on auditors' ethical behavior. The study involved 46 auditors from a public accounting firm in Central Jakarta, using purposive sampling. Both quantitative and descriptive statistical methods, along with multiple linear analysis, were employed. Data was collected through a questionnaire assessing internal control, compliance, management compensation, work ethic, and auditors' ethical behavior. Findings reveal that internal control and compensation significantly influence auditors' ethical behavior. However, management compensation alone does not have a significant effect. Work ethic also has a substantial impact on ethical behavior. Collectively, internal control, compliance, management compensation, and work ethic significantly affect auditors' ethical behavior. Managerial implications include the necessity for robust internal control systems to prevent unethical conduct and designing management compensation structures that do not incentivize unethical behavior.